Smith’s predictor for congestion control in TCP Internet protocol - S. Mascolo (Proceedings of the 1999 American Control Conference (Cat. No. 99CH36251), 1999)
The Transfer Control Protocol/Internet Protocol (TCP/IP) was originally designed to provide reliable data delivery over conventional networks for a limited range of transmission rates and propagation delays. One of TCP/IP key functions is its congestion control mechanism. Nowadays, the ever-increasing transmission speed of communication links is shifting the domain for which TCP was originally engineered. In particular, propagation delays could have an adverse impact on the stability of feedback control algorithms in high speed communications. We design an algorithm for congestion control in high-speed Internet using a Smith predictor. The proposed control law is effective over connection paths with any bandwidth-delay product. Moreover, it leads to a simple generalization of the today’s TCP congestion control algorithm by using a generalized advertised window (GAW). TCP using GAW can be easily implemented in the real Internet and is completely backward compatible allowing GAW routers to interact with non-GAW routers.
Keywords: Internet; Protocols; Communication system control; TCPIP; Propagation delay; IP networks; Telecommunication network reliability; Reliability engineering; Stability; Feedback control